Synthesis of bis(indolyl) methanes Using Environmentally Favorable Cellulose Supported Sulfanilic Acid Catalyst (International Journal of Scientific Research in Science and Technology, 2025)
Cellulose sulfanilic acid is a highly regarded catalyst for producing bis(indolyl)methanes. In this process, a substituted benzaldehyde interacts with two indole molecules to form a biologically active bis(indolyl)methane compound. The reaction is rapid and utilizes a readily available, cost-effective, environmentally friendly, solvent-free, and green catalyst. This catalyst facilitates the activation of the carbonyl group in the aldehyde, which then reacts with the third position of the indole molecule.
Keywords: bis(indolyl)methanes; biologically active; cellulose; sulphanilic acid